Management Practices, Planning, and Education Policy in Indonesia and Malaysia - Muchtar, Margane Naasika Islamic; Sultoni, Sultoni (Universitas Negeri Malang, 2024)
This study aims to explore and compare the intricate web of management practices, planning strategies, and educational policies that have shaped these two countries' educational systems. This study employs a mixed-methods approach, combining qualitative and quantitative research methodologies, to provide a comprehensive analysis of the educational systems in Indonesia and Malaysia. It seeks to unravel the complex tapestry of educational management practices in both countries, exploring how decisions are made and implemented across different levels of governance. The collected data was subjected to a rigorous analysis process, employing both quantitative and qualitative techniques. The findings of this study reveal that while both countries have adopted different approaches to educational management and policy implementation, reflecting their unique historical, cultural, and geographic contexts, they share common goals of improving educational quality, access, and relevance. The insights gained from this comparative analysis can inform policy decisions and contribute to the broader discourse on education in developing nations.